Morbidities and mortality of diagnosed attention deficit hyperactivity disorder (ADHD) over the youth lifespan: A population‐based retrospective cohort study - Diallo, Fatoumata Binta; Pelletier, Éric; Vasiliadis, Helen‐Maria; Rochette, Louis; Vincent, Annick; Palardy, Sylvain; Lunghi, Carlotta; Gignac, Martin; Lesage, Alain (International journal of methods in psychiatric research, 2022)
Objectives To estimate the prevalence of ADHD, and related comorbidities, mortality, and type of health service use among children and young adults, using different case definitions. Methods We conducted a population‐based retrospective cohort study between 2000 and 2018, using the Quebec Integrated Chronic Disease Surveillance System (QICDSS) database. All residents aged less than 25 years eligible for health insurance coverage were included. We compared outcomes of three indicators (morbidity, services use and mortality) according two different algorithms of ADHD definitions, to the general population. Results The cumulative prevalence of ADHD has risen steadily over the past decade, reaching 12.6% in 2017–2018. People with ADHD have a higher prevalence of psychiatric comorbidities, make greater use of medical, mental health services, and are hospitalized more often. The comparison of prevalence between the two algorithms and the general population for the three indicators showed that the cohort having one claim was very close to that with two or more, and statistically significant higher to that of people without ADHD. Conclusion This finding support that a single claim algorithm for ADHD can be used for case definition. More research is needed on the impact of potentially effective treatments in improving consequences of ADHD.